THE INFLUENCE OF CUTTING THICKNESS, SHAPE AND MOISTURE CONTENT ON OIL ABSORPTION DURING POTATO FRYING - Paunović, Dragana M.; Marković, Jovana M.; Stričević, Lazar P.; Vujasinović, Vesna B.; Rabrenović, Biljana B. (Journal of Agricultural Sciences (Belgrade), 2021)
Potato chips and French fries are products which are often used in the human diet. The aim of this study was to investigate the influence of cutting thickness, shape and moisture content on palm olein uptake, as well as the quality of the palm olein during the production of fried potatoes. Blanching operation was conducted in water for 3 minutes at a temperature of 85oC, while the frying process was conducted in palm olein for 3 minutes at a temperature of 165oC. The peroxide value and free fatty acids content (% oleic acid) was determined by standard analytical methods. The oil content in samples was determined by the standard Soxhlet extraction (reference method). The results showed that the potato chips had approximately four times more oil uptake compared to potato sticks. The oil content was significantly lower in blanched potato slices (by 43.3%), but significantly higher in blanched potato sticks (by 53.5%), compared to unblanched samples. The analysed quality parameters of palm olein were within the allowable value range. Based on the results obtained in this study, it can be concluded that the thickness, surface area and moisture content of the potato had a significant effect on oil uptake.